The 2019 Netherlands Model BIT: riding the new investment treaty waves. (30th September 2019) - Duggal, Kabir A N; van de Ven, Laurens H
Abstract: Investor–state arbitration is undergoing a paradigm shift with several countries and regional blocs rethinking the best way to protect investor rights while retaining sovereign prerogatives. This is where the Netherlands fits into the narrative. Its decision to modernize appears to follow the contemporary developments in investment arbitration, including heightened public scrutiny on the effect of investment treaties on regulatory space and the investor-to-state dispute settlement system, as well as the Post-Treaty of Lisbon European Union framework for investment arbitration. On 16 May 2018, the Dutch Ministry of Foreign Affairs published a draft for a new Model Bilateral Investment Treaty (BIT) on the Government's website. This was done with a view to updating the earlier Model BIT which dates. Through public consultation, individuals and interest groups were invited to share their views. The Government amended the 2018 Draft Model BIT after deliberating on the public reactions it had received, and circulated a new draft on 19 October 2018. Subsequently, after parliamentary debate in February 2019, the Dutch Government published an updated Model BIT on 22 March 2019. In this article, we critically examine the 2019 Final Dutch Model BIT and examine it in light of the global rethink on investment law and policy.